Body composition analysis by bioelectrical impedance and its relationship with nutritional status in older adults-a cross sectional descriptive study: Body composition in older adults - Alhamdan, Adel; Al-Muammar, May; Bindawas, Saad; Alshammari, Sulaiman; Al-Amoud, Maysoon; Calder, Philip (Progress in Nutrition, 2021)
Objective: Measuring body composition gives an indication of the health status of older adults. To the best of our knowledge, there is no detailed investigation performed to assess body composition and its relationship with nutritional status in older adults, particularly in community-dwelling older adults. Thus, the aim of the study is to assess body composition and its relationship with nutritional status in older adults. Methods: A cross-sectional descriptive study with a multistage stratified sampling design was carried out in community-dwelling older adults in Riyadh city, the capital of the Kingdom of Saudi Arabia. Bioelectrical impedance analysis was used to analyze body composition. Furthermore, the association between body composition and nutrition status [assessed using the mini-nutritional assessment (MNA®) tool], was determined. Results: There were significant differences between older men and women with respect to body composition. Percentage body fat (PBF), fat mass, and fat mass index (FMI) were strongly positively correlated with body mass index (BMI). Those who were classified as malnourished had significantly lower BMI, PBF, fat mass, FMI, fat-free mass, and muscle mass compared to those classified as at risk of malnutrition or well-nourished. Multiple logistic regression highlighted the positive impact of various body composition measures on nutritional status. Calf circumference ˃31cm, significantly decreased the odds ratio (OR) of being malnourished (OR 0.055, C.I. 0.037-0.082). Conclusions: There are differences in body composition between older men and older women, and there is an association between body composition and nutritional status in older adults.